Pemberdayaan Badan Usaha Milik Desa (BUMDes) Bhuhi Wahi melalui Penguatan Tata Kelola dan Edukasi Masyarakat di Kampung Puay, Distrik Sentani Timur, Kabupaten Jayapura (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service article reports the implementation of the Thematic Community Service Program (KKN) by Group 16 of Universitas Cenderawasih in Puay Village, East Sentani District, Jayapura Regency, focusing on strengthening the governance of the Village-Owned Enterprise (BUMDes) Bhuhi Wahi. The program aimed to compile village and BUMDes profile data, provide governance assistance, and educate the community about the concept and management of BUMDes. The methods included participatory observation, in-depth interviews with village officials and BUMDes administrators, cost structure analysis, and community outreach. The results showed that of the three planned business units, namely a refill drinking water depot, fisheries, and agriculture, only the water depot was active. This unit still faced a gap between its formal organizational structure and daily management practices. Estimates of the Cost of Goods Manufactured and break-even point indicated that the business unit had not consistently reached the break-even point at low to moderate production volumes. The outreach activities improved the understanding of village officials, customary leaders, and women's groups regarding BUMDes governance. The outputs included a customary structure chart, village map, and information banner for the water depot. The program recommends systematic bookkeeping, alignment between formal structures and management practices, and continuous assistance to support the financial sustainability of the business unit.